Design and experimental validation of a robust dual-loop Smith predictor controller for stable and integrative systems - Fergani, Nadir; Allad, Mourad (Archives of Control Sciences, 2026)
ime-delay systems, which are widely encountered in industrial processes, pose significant challenges to controller design due to their complex dynamics and their limited robustness margins. This paper presents introduces an explicit design methodology for a robust Smith predictor-based control structure employing a fully isolated dual-loop configuration. The proposed controller combines integer and fractional order dynamic operators to enhance robustness against plant uncertainties while maintaining favorable dynamic performance. The effectiveness of the proposed approach is demonstrated through simulation studies on various integrative process models, including comparative analysis with several recent control techniques. Furthermore, experimental validation on a liquid level control system representative of FOPTD industrial processes confirms the simulation findings, showing excellent reference tracking, effective disturbance rejection, and smooth control effort even under increased time delays. The results demonstrate the superior robustness and flexibility of the proposed design compared to existing methods, highlighting the practical benefits of the isolated dual-loop Smith predictor structure for real industrial applications.